SFM Fetal Therapy Practice Guidelines: Fetal Fluid Aspiration - Gupta, Sangeeta; Batra, Meenu (Journal of Fetal Medicine, 2023)
Fetal fluid aspiration is commonly required from the pleural cavity or bladder and is termed as thoracocentesis or vesicocentesis, respectively. These procedures are performed for diagnostic and therapeutic indications. A detailed pre-procedure counseling and informed consent of the patient are necessary explaining the procedure and risks involved. These can be performed under aseptic precautions using ultrasound guidance with the help of 22-gauge needle.
Keywords: informed consent; thoracocentesis; ultrasound; vesicocentesis